Control de pudrición blanca (Sclerotium cepivorum) en bulbillos de ajo (Allium sativum) variedad colorado para reproducción de plantas - Capuz Bravo, Nelson Javier (2013)
The present investigation was to evaluate the control of white rot (Sclerotium cepivorum) in bulblets of garlic (Allium sativum) red variety for plant breeding. Fungicides applied were: Vitavax 300, Benomyl and Captan 80%. The research work was conducted in the Canton Ambato, Tungurahua Province, Santa Rosa parish, community Angahuana Low, owned by Mr. Nelson Javier Bravo Capuz; in GPS coordinates, Latitude South of 1°19'59'' and Longitude West of 78°41'37'' Southern Hemisphere; (WGS84 UTM 756652 North and 9852518 East). The experimental design used was a D.B.C.A. (Design of a Randomized Complete Block) with 4 treatments and 5 replications. The best treatment is the T1 (7 g.L-1 of water of Vitavax 300). Economic analysis shows that treatment with lower cost of production/plant with a value of U$D 0,03 are the treatments: T1 (7 g.L-1 of water of Vitavax 300), T2 (0,5 g.L-1 of water of Benomyl) and T3 (1,5 g.L-1 of water of Captan 80%), and higher treatment cost of production/plant is U$D 0,04 T4 (Witness).